The Correlation between Family Support with the Quality of Life of Patients with Diabetes Mellitus - Retnowati, Nilla; Satyabakti, Prijono (Faculty of Public Health, 2015)
ABSTRACTDiabetes mellitus is a disease that will accompany a lifetime and require long term treatment so that it can reduce quality of life of the patients. This study aim to analyze the correlation between family support with the quality of life of patients with diabetes mellitus. This study was analytic observational with cross-sectional design. The population was all patients with diabetes mellitus who visited Tanah Kalikedinding Health Center in January to March 2014. Patients was diagnosed diabetes mellitus through laboratory test using blood serum venous plasma. The number of respondents was 45 respondents that were chosen using simple random sampling method. Variables studied were family support, respondentâs characteristics (age, gender, education level, income, marital status and employment status), duration of diabetes, diabetes complications and quality of life. The results of Chi-square test with continuity correction Fisherâs exact test showed that variables that were significantly correlated with the quality of life such as family support (p=0.000), education level (p=0.039), income (p=0.034), marital status (p=0.003) and diabetes complications (p=0.007). The results of Mantel- Haenszel test showed that all the studied variables were confounding the correlation between family support with the quality of life. Confounding variable that have the greatest contribution was diabetes complications. The conclusion is that family support is significantly correlated with the quality of life of patients with diabetes mellitus in Tanah Kalikedinding Health Center. Health centers are expected to carry out health promotion and health education programs for patients with diabetes mellitus and their families to improve the quality of life of the patients.Keywords: diabetes mellitus, quality of life, family support, diabetes complications, marital status